The impact of electricity tariffs on residential demand side flexibility - Marian Hayn; Valentin Bertsch; Anne Zander; Stefan Nickel; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2016)
Energy systems based on renewable energy sources require increasing demand side flexibility. Also, changes in the underlying cost structure, i. e., decreasing variable costs and increasing infrastructure investments, and varying customer needs should be reflected in the setup of future markets, including retail markets and electricity providers' tariffs. While various studies focus solely on tariffs with variable energy prices to leverage residential demand side flexibility, we incorporate tariffs with a variable capacity price component in our analysis. The latter enables electricity providers to offer more differentiated tariffs, considering individual customer needs and a balanced cost allocation. To compare the impact of different tariffs on residential demand side flexibility, we develop a bottom-up load model. This model not only simulates but also optimizes residential load profiles according to different tariffs. In order to account for behavioral aspects, the model is calibrated based on data from a large-scale field trial. Our results show that tariffs with variable energy prices induce larger demand side flexibility, but the impact of tariffs with variable capacity prices is more predictable and reliable from a supplier's point of view. To enable sustainable business models, politics should change regulations rewarding demand side flexibility and facilitating the technical implementation.
urn:nbn:de:swb:90-547123
Keywords: 330; Residential bottom-up load model; variable energy prices; variable capacity prices; load shifting potential